Norme pro-environnementale et participation : entre adhésion et clairvoyance normative (une étude comparée entre habitants d'écoquartier et habitants de quartier ordinaire) - Didier Laugaa; Grégoire Le Campion (Développement Durable et Territoires)
The dimension taken by ecology-related issues is revealed in the establishment of a dominant ideology essentially prescriptive in nature. From this a new social norm has appeared : the pro-environmental norm. More than just recommending Ecologically Responsible Behaviour, prevailing opinion insists that inhabitants become involved on a grand scale in the life of their neighbourhood. This demand for participation is particularly apparant in urban Eco-neighbourhood projects. The comparison of two groups of 100 inhabitants (of an Eco-neighbourhood and a traditional one) shows that Eco-neighbourhood inhabitants have a greater normative clear-sightedness than the others. This means that they are better acquainted with the socially valorising nature of pro-ecological attitudes. This clear-sightedness is especially apparant on the issue of local involvement in neighbourhood life. However, the high level of clear-sightedness leads us to question how much credit can be given to the answers of eco-neighbourhood inhabitants concerning their involvement in ecologically responsible behaviour and the true level of their participation in local life.